Multiscale Modeling of Thiol Overoxidation in Peroxiredoxins by Hydrogen Peroxide - Semelak, Jonathan Alexis (2019)
In this work, we employ a multiscale quantum-classical mechanics (QM/MM) scheme to investigate the chemical reactivity of sulfenic acids toward hydrogen peroxide, both in aqueous solution and in the protein environment of the peroxiredoxin alkyl hydroperoxide reductase E from Mycobacterium tuberculosis (MtAhpE). The reaction of oxidation of cysteine with hydrogen peroxides, catalyzed by peroxiredoxins, is usually accelerated several orders of magnitude in comparison with the analogous reaction in solution. The resulting cysteine sulfenic acid is then reduced in other steps of the catalytic cycle, recovering the original thiol. However, under some conditions, the sulfenic acid can react with another equivalent of oxidant to form a sulfinic acid. This process is called overoxidation and has been associated with redox signaling. Herein, we employed a multiscale scheme based on density function theory calculations coupled to the classical AMBER force field, developed in our group, to establish the molecular basis of thiol overoxidation by hydrogen peroxide. Our results suggest that residues that play key catalytic roles in the oxidation of MtAhpE are not relevant in the overoxidation process. Indeed, the calculations propose that the process is unfavored by this particular enzyme microenvironment.